Efficacy of the Aussie Optimism Program: Promoting Pro-social Behavior and Preventing Suicidality in Primary School Students. A Randomised-Controlled Trial - Roberts, Clare M.; Kane, Robert T.; Rooney, Rosanna M.; Pintabona, Yolanda; Baughman, Natalie; Hassan, Sharinaz; Cross, Donna; Zubrick, Stephen R.; Silburn, Sven R. (Frontiers in Psychology, 2018)
The efficacy of an enhanced version of the Aussie Optimism Program was investigated in a cluster randomised control trial. Grade 6 students aged 10 – 11 years of age (N = 2288) from 63 government primary schools in Perth Western Australia, participated in the pre, post and follow-up study. Schools were randomly assigned to one of three conditions: Aussie Optimism with teacher training, Aussie Optimism with teacher training plus coaching, or a usual care condition that received the regular Western Australian Health Education Curriculum. Students in the Aussie Optimism conditions received 20, 1- hour lessons relating to social and interpersonal skills and optimistic thinking skills over the last two years of primary school. Parents in the active conditions received a parent information booklet each year, plus a self-directed resilience program in Grade 7. Students and parents completed the Extended Strengths and Difficulties Questionnaire. Students who scored in the clinical range on the Emotional Problems Scale were given The Diagnostic Interview for Children and Adolescents IV, to assess suicide ideation and behaviour, and depressive and anxiety disorders. Results indicated that the Aussie Optimism with teacher training plus coaching was associated with the best outcomes: A significant increase in student-reported pro-social behaviour from pre-test to post- test 1 (maintained at post-test 2) and significantly lower incidence rates from suicidal ideation at post-test 2 and follow-up. No significant intervention effects on anxiety and depression disorders, and total difficulties were reported. These findings suggest that the Aussie Optimism Program with Teacher Training along with Coaching may have the potential to positively impact on suicidality and pro-social behavior in the pre-adolescent years.